Neutrophil/Lymphocyte Ratio as a Biomarker of Response to H1-Antihistamine Therapy in Patients with Chronic Spontaneous Urticaria - Xiaonan Qiu; Qiao Ran; Juanjuan Pan; Guozhen Tan (Indian Journal of Dermatology)
Backgrounds A large proportion of patients with chronic spontaneous urticaria (CSU) are resistant to a standard dose of antihistamine. Acknowledged biomarkers for identifying these patients have not been determined. The neutrophil/lymphocyte ratio (NLR) has been considered as an important indicator of inflammation in chronic diseases. Aims To explore whether NLR could serve as a biomarker for predicting the response to H1-antihistamine in patients with CSU. Methods This hospital-based, retrospective study included 109 patients with CSU diagnosed from 2017 to 2020 in our clinic and divided them into two groups by their responses to the 2-week antihistamine therapy of standard-dose: 69 with H1-antihistamine-refractory and 40 with non-H1-antihistamine-refractory CSU. The laboratory test results were collected from the hospital information system and integrated with SPSS software. Results Patients refractory to H1-antihistamine had significantly higher median NLR (P = 0.039), age (3 P = 0.021), complement C3 (P = 0.026), presence of elevated WBC (P = 0.026) and elevated monocytes (MONO) (P = 0.045) and significantly lower IgM (P = 0.022). The binary logistic regression model revealed that NLR was significantly associated with H1-antihistamine-refractory of CSU (odds ratio (OR) 1.717, 95% confidence interval (CI) 1.065–2.766, P = 0.026), which was consistent with that after adjusted for potential confounding factors including age, complement C3, presence of elevated WBC and MONO, and IgM (OR 1.681, 95% CI 1.019–2.773, P = 0.042). Conclusion Our results showed a strong and significant association between higher NLR and H1-antihistamine resistance in CSU, suggesting that NLR may be a potential biomarker for predicting the response to H1-antihistamine therapy in patients with CSU.